2010
DOI: 10.1002/app.32998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure of curing agents modified by epoxidized oleic esters on the toughness of cured epoxy resins

Abstract: The aim of this study was to determine the effect of the ester carbon chain length of curing agents modified by epoxidized oleic esters on the toughness of cured epoxy resins. An amine-terminated prepolymer (i.e., curing agent G) was synthesized from a bisphenol A type liquid epoxy resin and triethylene tetramine. The toughening curing agents (G1 and G2) were prepared by reactions of epoxidized oleic methyl ester and epoxidized oleic capryl ester, respectively, with curing agent G. Fourier transform infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Because of the small addition of DGEBAEO‐6, EB‐1 exhibited a relatively rougher crack surface compared to the neat DGEBA. The fracture surface of EB‐2 became further rougher with some ridges, which acted as obstacles to cause the deflection of the crack; hence, the required energy for the propagation of the cracks on the fracture surfaces increased 33. However, there was not obvious plastic deformation on the surface, indicating the brittle fracture characteristic of EB‐2.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the small addition of DGEBAEO‐6, EB‐1 exhibited a relatively rougher crack surface compared to the neat DGEBA. The fracture surface of EB‐2 became further rougher with some ridges, which acted as obstacles to cause the deflection of the crack; hence, the required energy for the propagation of the cracks on the fracture surfaces increased 33. However, there was not obvious plastic deformation on the surface, indicating the brittle fracture characteristic of EB‐2.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported on the epoxidized soybean oil (ESO) based epoxy blends for its toughening nature . Similarly esterified soybean oil based epoxy blends with improved properties has been reported by Wang et al, Zhu et al ., and Cheng et al, Haq et al ., and Sahoo et al . in recent years.…”
Section: Introductionmentioning
confidence: 82%
“…This suggested that no large scale plastic deformation occurred during fracture, which was typical of a brittle thermosetting polymer; hence, a low impact strength of 10.02 kJ/m 2 was measured. For comparison, the fracture surface of TGAPP/DDS was rougher than that of the TGPAP/DDS, the ridges on the fracture surface acted as obstacles to cause the deflection of the crack, therefore, the required energy for the propagation of the cracks on the surfaces increased . As a result, the impact strength of TGAPP/DDS was increased by 50% to 15.10 kJ/m 2 .…”
Section: Resultsmentioning
confidence: 99%